IDENTIFICATION OF BACTERIAL WILT AND LEAF BLIGHT DISEASE ON MAIZE (Zea mays) FOUND IN KEDIRI, INDONESIA - Aini, Luqman Qurata; Suryani, Lilis; Sugiharto, Arifin Noor; Abadi, Abdul Latief (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2013)
Recently, a new bacterial disease of maize (Zea mays) was observed in Kediri, East Java, Indonesia. Infected plants showed wilt symptoms occasionally accompanied by leaf blight. This study aims to characterize the causal agent of bacterial wilt and leaf blight of maize observed in Kediri. Gram-negative, facultative anaerobic bacteria were isolated from the diseased tissues. All bacterial strains (KD1A, KB2A, KD1, KD4, KB1) gave positive result both in the hypersensitive response and pathogen-nicity assays. However, only KD1 and KB1 strains could be re-isolated from the diseased tissues. Based on several physiological and biochemical assays, the bacteria resembled Pantoea agglomerans. Moreover, the strains showed negative result on PCR amplification using HRP1d and HRP3r, a primer pair specific for detection of P. stewartii subsp. stewartii. Analysis of 16S rRNA gene sequence of KD1 and KB1 showed highest homology at 88% and 90%, respectively to P. agglomerans strain DSM 3493 (NR 0419781).Â The homology values were too low to conclude that the bacteria were similar to P. agglomerans. These results suggest that bacterial pathogens isolated from maize in Kediri were strains of Pantoea sp. Keywords: maize, Pantoea sp., wilt, leaf blight